Deposition of micrometer-sized aerosol particles in neonatal nasal airway replicas. Issue 4 (3rd April 2018) - Tavernini, S.; Church, T. K.; Lewis, D. A.; Noga, M.; Martin, A. R.; Finlay, W. H.
ABSTRACT: The nasal aerosol filtration properties of infants 0–3 months old have been quantified through in vitro measurements. Computed tomography (CT) scan data was obtained of seven individuals with ages of 5–79 days. Nasal airway replicas based on these images were manufactured using rapid prototyping. Deposition in the replicas was measured using an electrical low pressure impactor (ELPI) to measure the concentration of aerosol particles in the inertial regime. Comparing the difference in concentration when sampling through the model versus sampling through a blank line gave the deposition fraction. Deposition was measured for particles with aerodynamic diameters between 0.53 and 5.54 μm. Nonlinear least squares curve fitting was performed to collapse intersubject variability and represent the data with a single curve. To achieve satisfactory intersubject variability collapse, a non-dimensional pressure drop, the Euler number ( Eu ), was required in addition to the Reynolds number ( Re ) and the particle Stokes number ( Stk ) where the dimensionless parameters are evaluated with a length scale, D, defined as the airway volume divided by the airway surface area. The equation describing the deposition fraction, η, is η = 1- (14590 / (14590 + Stk 1.2201 Re 1.7742 Eu 1.5772 )) 0.3687 . An analysis of the expected intersubject variability in in vivo deposition was also performed, yielding a method for predicting variance in neonatal nasal airway deposition. Copyright © 2018 American Association for Aerosol Research